Maternal cardiovascular health in early pregnancy and the risk of congenital heart defects in offspring - Dan-wei Zhang; Yi-bing Zhu; Si-jia Zhou; Xiu-hua Chen; Hai-bo Li; Wen-juan Liu; Zheng-qin Wu; Qiang Chen; Hua Cao (BMC, 2024)
Abstract Background Congenital heart disease (CHD) is the predominant birth defect. This study aimed to explore the association between maternal cardiovascular health (CVH) and the CHD risk in offspring. Methods We used the prospective data from the Fujian Birth Cohort Study, collected from March 2019 to December 2022 on pregnant women within 14 weeks of gestation. Overall maternal CVH was assessed by seven CVH metrics (including physical activity, smoking, sleep duration, body mass index, blood pressure, total cholesterol, and fasting plasma glucose), with each metric classified as ideal, intermediate or poor with specific points. Participants were further allocated into high, moderate and low CVH categories based on the cumulative CVH score. The association with offspring CHD was determined with log-binominal regression models. Results A total of 19810 participants aged 29.7 (SD: 3.9) years were included, with 7846 (39.6%) classified as having high CVH, 10949 (55.3%) as having moderate CVH, and 1015 (5.1%) as having low CVH. The average offspring CHD rate was 2.52%, with rates of 2.35%, 2.52% and 3.84% across the high, moderate and low CVH categories, respectively (P = 0.02). Adjusted relative risks (RRs) of having offspring CHD were 0.64 (95% CI: 0.45-0.90, P = 0.001) for high CVH and 0.67 (95% CI: 0.48-0.93, P = 0.02) for moderate CVH compared to low CVH. For individual metrics, only ideal total cholesterol was significantly associated with lower offspring CHD (RR: 0.73, 95% CI: 0.59-0.83, P = 0.002). Conclusions Pregnant women of high or moderate CVH categories in early pregnancy had reduced risks of CHD in offspring, compared to those of low CVH. It is important to monitor and improve CVH during pre-pregnancy counseling and early prenatal care.